Development of Project Based Teaching Module to Increase Students' Creativity in Designing Indonesian Language Learning - Wibowo, Setiawan Edi; Mustadi, Ali; ., Supartinah; Sugiarsih, Septia; Sayekti, Octavian Muning (Journal of Ecohumanism, 2024)
This research aims to produce a Project Based Teaching Module that is suitable for use in lectures on the Development of Indonesian Language and Literature Learning in elementary schools oriented to the Independent Curriculum. This type of research is R&D with an ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design. This research was carried out on S1 students of the PGSD FIPP UNY Study Program who are taking the Elementary Indonesian Learning Development Course. The data collection techniques that will be used in the study include teaching material assessment scales, observation sheets, and interview guidelines. The research instrument used in the design and develop stage is carried out on an assessment scale to test feasibility using a scale. The data analysis in this study was carried out in two ways, namely (1) the data from the interview was analyzed by descriptive-qualitative analysis techniques and (2) the product feasibility data. The results of the product assessment data were measured and analyzed by qualitative descriptive techniques using score scale conversion. After obtaining data in the form of scores, the next step is to convert quantitative data into qualitative data with a scale assessment classification of 5, namely very feasible, feasible, moderately feasible, less feasible, and very unfeasible. The result of this research is the production of a project-based teaching module that is feasible to increase students' creativity in designing Indonesian language learning in elementary schools. The implication of the results of this study is that designing lectures from scratch—contained in modules—makes it easier for students to understand and implement theory to become a product.